2013
DOI: 10.1002/bse.1791
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Quality, Environmental and Health and Safety Management by Car Manufacturers – a Long‐Term Empirical Study

Abstract: The diversity of stakeholder requirements is currently a pivotal challenge for companies. Stakeholders expect companies to increasingly consider environmental and social aspects in their decisions. Thus, corporate goal systems are including not only qualitative and financial goals, but also environmental and social ones. Management systems for ensuring quality, environmental and occupational safety play an important role in achieving these objectives. Considering the interdependency between the different syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 74 publications
0
35
0
3
Order By: Relevance
“…Based on the assumption that over time, firms have implemented different management systems increasing complexity and duplicating costs, some authors have highlighted how also integrating "managing the interdependence of quality, environmental and occupational health and safety management" could be a good solution [71] (p. 396). IMS have been defined as "a single integrated system used by an organisation to manage the totality of its processes, in order to meet the organisation's objectives and equitably satisfy the stakeholders" [72] (p. 3).…”
Section: Csfs Of Integrated Management Systemsmentioning
confidence: 99%
“…Based on the assumption that over time, firms have implemented different management systems increasing complexity and duplicating costs, some authors have highlighted how also integrating "managing the interdependence of quality, environmental and occupational health and safety management" could be a good solution [71] (p. 396). IMS have been defined as "a single integrated system used by an organisation to manage the totality of its processes, in order to meet the organisation's objectives and equitably satisfy the stakeholders" [72] (p. 3).…”
Section: Csfs Of Integrated Management Systemsmentioning
confidence: 99%
“…Martínez-Campillo, Head-García & Marbella-Sánchez, 2013), energy (Moseñe, Burritt, Sanagustín, Moneva & Tingey-Holyoak, 2013) and Public Administration (Bernal Conesa, De Nieves Nieto & Briones Peñalver, 2014;García-Sanchez Frias-Aceituno & Rodriguez-Dominguez, 2013) and even one that refers to technology companies (Guadamillas-Gómez, ; the possible motivations to adopt CSR (Prado- Lorenzo et al, 2008;, and its integration with other management systems in the company (Bernardo, 2014;Von Ahsen, 2014;Castka & Balzarova, 2008). However, no studies have been found on CSR, their motivations and integration technology companies, which are a constant source of innovation, not only in processes but also products.…”
Section: Csr and Spanish Technology Sectormentioning
confidence: 99%
“…En la literatura científica existen numerosos estudios sobre la RSC tanto en grandes empresas (Melé, Debeljuh & Arruda, 2006) , 2008;, y su integración con otros sistemas de gestión de la empresa (Bernardo, 2014;Von Ahsen, 2014;Castka & Balzarova, 2008); sin embargo, no se han encontrado estudios sobre RSC, sus motivaciones e integración en empresas tecnológicas, las cuales son fuente constante de innovación, tanto en procesos como en productos, por tanto, se considera escasa la información sobre el sector tecnológico, denotando que no han sido analizadas en profundidad las motivaciones de la RSC y su integración en el sistema de gestión de la empresa tecnológica, por ello se estima interesante profundizar en el estudio de la misma en empresas tecnológicas españolas, ya que investigaciones previas han demostrado que las organizaciones con una orientación estratégica hacia la innovación apuestan por mejorar sus capacidades organizativas internas para ser más competitivas en un entorno global (Suñe, Bravo, Mundet & Herrera, 2012). De hecho para fomentar las innovaciones de producto y proceso, las empresas deben adoptar prácticas formalizadas de RSC pues ésta tiene una contribución positiva en la competitividad (Boulouta & Pitelis, 2014).…”
Section: Rsc Y Sector Tecnológico Españolunclassified
“…Se encuentran además estudios sobre las posibles motivaciones de adoptar la RSC (Graafland & Schouten, 2012) de forma general y su integración con otros sistemas de gestión de la empresa (Bernardo, 2014;Von Ahsen, 2014). Sin embargo, no se han encontrado estudios sobre la RSC, sus motivaciones e integración en empresas tecnológicas, las cuales son fuente constante de innovación, tanto en procesos como en productos, ya que el estudio del papel de las empresas tecnológicas en la gestión ambiental, la sostenibilidad y por tanto en la RSC está aún en sus etapas iníciales (Wang, Chen, & BenitezAmado, 2015).…”
Section: Revisión De La Literaturaunclassified